THE USE OF GROUP INVESTIGATION (GI) TECHNIQUE ON STUDENTS' READING COMPREHENSION - Nurlailiah, Ai (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
Reading is one of the primary skills that students must learn. In reading comprehension, they should not only read the whole text, but also comprehend what the important point of the text is. However, they will face some difficulties comprehending text during reading. Therefore, Group Investigation (GI) technique is the solution to solve their difficulties. The aim of the research is to investigate the effect of Group Investigation (GI) technique on students reading comprehension. In conducting the research, the researcher used a pre-experimental design in a one-group pretest-posttest design using a quantitative approach. The population of the research was the students of XI grade of SMK Qotrunnada Al-Ilmi. There were 15 students in the sample, which was taken by simple random sampling. The students were given a reading comprehension test as the instrument. The result showed that based on the t-tabel, the t-test value result is 8.7, and the degree of freedom (df) of 14 at the level of significance 0.05 is 2.14. Then, the t-test value result is higher than the t-table value (8.7 2.14). It means that the alternative hypothesis of this research (Ha) is accepted. It can be concluded that Group Investigation (GI) is one technique to help students in comprehending the text. In other words, Group Investigation (GI) techniques affect students reading comprehension.